AKU DALAM KARYA SENI LUKIS - TAUFIK HIDAYAT, Yasrul Sami, S.Sn., M.Sn., Drs. Idran Wakidi, M.Pd. (Universitas Negeri Padang, 2017)
The purpose of the creation of this final work is to convey the message of experience in life, especially in the social environment through feelings of joy and sorrow into the work of painting using the technique of pointelism. I am here closely related to one's outpouring of the various emotions that are felt. I am here closely related to one's outpouring of the various emotions that are felt. The emotional upheaval can affect the attitudes, actions and behavior of a person in living life. The method of creation of the work uses five stages: preparation stage, elaboration stage, synthesis stage, concept realization stage.Kata Kunci: Aku, Dalam Karya, Seni Lukis